X-RAY SEMIOTICS OF ENDOCRINE OPHTHALMOPATHY. PART 2. THE OPTIC NERVE, LACRIMAL GLAND, SUPERIOR OPHTHALMIC VEIN - O. Yu. Yatsenko; I. E. Tyurin (Вестник рентгенологии и радиологии, 2017)
Objective: to study the optic nerve, lacrimal gland, and superior ophthalmic vein in patients with different clinical forms of endocrine ophthalmopathy (EOP). Material and methods. 294 patients (559 orbits) with EOP were examined. Hydrodynamic disorders were detected in 43 patients. 46 patients (91 orbits) with mixed or myogenic types of edematous exophthalmos (EE) were diagnosed as having optic neuropathy (ON). Results and discussion. The paper presents the indicators of the optic nerve, lacrimal gland, and superior ophthalmic vein in patients with different clinical forms of EOP. This study provides evidence that ON in patients with EOP is characterized by specific changes in the optic nerve, as shown by computed tomography. It is ascertained that there are volumetric and structural changes in the lacrimal gland in 40.62% of the patients with mixed EE and in 33.89% of those with myogenic EE. Conclusion. The study of the extraocular muscles in patients with ON-complicated EE may confirm that enlargement of the extraocular muscles at the orbital apex plays a major role in the pathogenesis of ON in this disease. The change in the anatomictopographic relationships of the orbit leads to compression of the superior ophthalmic vein, which entails obstruction of blood outflow from the orbit and causes ocular hypertension.